2021
DOI: 10.3390/biomedicines9020195
|View full text |Cite
|
Sign up to set email alerts
|

LAT1 and ASCT2 Related microRNAs as Potential New Therapeutic Agents against Colorectal Cancer Progression

Abstract: The development and progression of colorectal cancer (CRC) have been associated with genetic and epigenetic alterations and more recently with changes in cell metabolism. Amino acid transporters are key players in tumor development, and it is described that tumor cells upregulate some AA transporters in order to support the increased amino acid (AA) intake to sustain the tumor additional needs for tumor growth and proliferation through the activation of several signaling pathways. LAT1 and ASCT2 are two AA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…A vast number of studies have demonstrated that the expression of amino acid transporters LAT1 and ASCT2 is enhanced in tumor tissues, e.g., colorectal cancer, suggesting a crucial role of amino acid supply in fulfilling the high proliferation rate in cancer cells [ 66 ]. However, scarce information is available concerning the relationship of amino acid transporter expression with cell growth in human ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A vast number of studies have demonstrated that the expression of amino acid transporters LAT1 and ASCT2 is enhanced in tumor tissues, e.g., colorectal cancer, suggesting a crucial role of amino acid supply in fulfilling the high proliferation rate in cancer cells [ 66 ]. However, scarce information is available concerning the relationship of amino acid transporter expression with cell growth in human ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In colorectal cancer, miR-3199 was screened as a downregulated DEmiRNA. 21 As common differentially expressed lncRNA and miRNA in colon cancer, 22 , 23 the functions and functional mechanism of LINC01006 and miR-3199 in colon cancer have not been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…One subtype of treatment-resistant colorectal cancer, KRAS mutated, is associated with increased expression of ASCT2 8 . Both ASCT2 and LAT1 are investigational targets for future therapies, including microRNA treatment 9 . Both prostate and colorectal cancers have been linked to dietary and genetic factors with ongoing research in these areas 10 …”
mentioning
confidence: 99%
“…8 Both ASCT2 and LAT1 are investigational targets for future therapies, including microRNA treatment. 9 Both prostate and colorectal cancers have been linked to dietary and genetic factors with ongoing research in these areas. 10…”
mentioning
confidence: 99%